Ergonomic Redesign in Scrap Area to Reduce the Risk of Cumulative Trauma Disorders and to Increase Capacity at Toy Manufacturing Company - Hery Hamdi Azwir; Jsslyn Jsslyn; Herwan Yusmira (President University, 2024)
In the auto rooting area, rejected rooted heads undergo scrap process before being discarded. A solder is currently used, which only destroys both eyes and thus, may increase the risk of rework done by irresponsible parties. A new tool using a toggle is preferable as it is more effective in removing the entire face. However, the toggle has a smaller capacity compared to the solder, which prevents the full transition. Upon observation, it is found that there are many non-ergonomic and non-value-added activities. This resultingly increases the risk of Cumulative Trauma Disorders (CTDs), particularly carpal tunnel syndrome, and reduces toggle capacity. Anthropometry and Rapid Upper Limb Assessment (RULA) are used to analyze the current posture and dimension. The method used to redesign the scrap workstation is Quality Function Deployment (QFD). The results of this study are that using, the newly improved workstation reduces RULA score from 6 to 2. Based on Nordic Body Map, the operator only feels pain in one body part, compared to the five body parts before improvement. By changing the pinch grip to a power grip, risks associated with carpal tunnel syndrome are minimized. Toggle capacity also increases by 49% from 300 to 448 rooted heads.